Demand for Information on Environmental Health Risk, Mode of Delivery, and Behavioral Change : Evidence from Sonargaon, Bangladesh - Tarozzi, Alessandro; Maertens, Ricardo; Ahmed, Kazi Matin; van Geen, Alexander (World Bank, Washington, DC, 2020)
Millions of villagers in Bangladesh are exposed to arsenic by drinking contaminated water from private wells. Testing for arsenic can encourage switching from unsafe wells to safer sources. This study describes results from a cluster randomized controlled trial conducted in 112 villages in Bangladesh to evaluate the effectiveness of different test selling schemes at inducing switching from unsafe wells. At a price of about USD0.60, only one in four households purchased a test. Sales were not increased by informal inter-household agreements to share water from wells found to be safe, or by visual reminders of well status in the form of metal placards mounted on the well pump. However, switching away from unsafe wells almost doubled in response to agreements or placards relative to the one in three proportion of households who switched away from an unsafe well with simple individual sales.